Pengenalan teknik Pembuatan Kapsul Black Garlic di Desa Sembalun Bumbung - Sopiati Alawiyah; Mia Maharani Dewi; M. Sarjan (Unram Journal of Community Service, 2020)
Introducing an appropriate technology  by University of Mataram  student group of KKN ( Kuliah Kerja Nyata) or Community Service program  was conducted in Sembalun Bumbung village Sembalun District, East Lombok Regency, West Nusa Tenggara Province. One of the aim of this program is to improve the added values of local existing product suchof  as “Black Garlic” that was modified into  into Black Garlic Capsules.  The program targeted partners of farmer groups, youths, and PKK (Pendidikan Keseahteraan Keluarga) group  by providing information on knowledge transfer and fermented garlic skill becomes a food product ( Black Garlic Capsules) as the prospective  business opportunity to increase the economy of the local community. The methods used in  this program including  the steps as follows , Intoducing the research on the development of black garlic, the demonstration and training on product manufacture , packaging and marketing training, assisting and mentoring to partnership and conducting evaluation during training. The result of this  program showed a positive response from village officials and its local people as c indicated byan be seen from  the enthusiasm of the participant during the training and actively  involved in the partnership. In addition, from this program indicated that the rapid knowledge improvement of the partnership on producing Black Garlic, the skill and capability improvement in practicing the processed product by the partnership , as well as  it makes them interested to produce  black garlic capsules to gain  additional income for their family.